Correlation relationships between sorbitol clearance indices and “classical” biochemical parameters of liver function in cattle - Ponamarev Vladimir (BIO Web of Conferences)
The work revealed correlations between sorbitol clearance rates and biochemical parameters in cattle. During the study, the sorbitol level in the urine of cattle and biochemical blood parameters were determined. Statistical processing of the obtained results was carried out using the methods of Pearson, Spearman and Fechner. A moderate positive relationship was found between the sorbitol level and biochemical parameters of the liver panel. It was confirmed that sorbitol can serve as a marker of the functional state of the liver. It was found that sorbitol clearance is directly related to the activity of liver enzymes. The further path for scientific research of the clearance of sorbitol and other compounds, as well as the improvement of diagnostic methods for liver pathologies are proposed.